Towards Collaborative Query Planning in Multi-party Database Networks - Zhao, Mingyi; Liu, Peng; Lobo, Jorge (Data and Applications Security and Privacy XXIX, 2015)
Multi-party distributed database networks require secure and decentralized query planning services. In this work, we propose the collaborative query planning (CQP) service that enables multiple parties to jointly plan queries and controls sensitive information disclosure at the same time. We conduct several simulated experiments to evaluate the performance characteristics of our approach compared to other planning schemes, and also study the trade-off between information confidentiality and query plan efficiency. The evaluation shows that when sharing more than 30 % of query planning information between coalition parties, the CQP service is able to generate reasonably efficient query plans. We also outline potential improvements of the CQP service at the end.